2000
DOI: 10.1063/1.125659
|View full text |Cite
|
Sign up to set email alerts
|

Fusion bonding of Si wafers investigated by x ray diffraction

Abstract: The interface structure of bonded Si(001) wafers with twist angle 6.5 ° is studied as a function of annealing temperature. An ordered structure is observed in x-ray diffraction by monitoring a satellite reflection due to the periodic modulation near the interface, which results from the formation of a regular array of screw dislocations. This satellite reflection first appears at an annealing temperature of 800 °C, and increases abruptly up to temperatures of 1000 °C. We propose that this transition occurs whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In other words, the bonding interface can be considered as silicon with some small pores distributed in the interfacial plane. These results are in agreement with the observation of the chemical changes reported in the literature between 500˚C and 700˚C [1], and with the creation of the dislocation networks at about T = 800˚C [9]. The evolution of the bonding interface thickness was also calculated.…”
Section: Temperature Investigationsupporting
confidence: 90%
“…In other words, the bonding interface can be considered as silicon with some small pores distributed in the interfacial plane. These results are in agreement with the observation of the chemical changes reported in the literature between 500˚C and 700˚C [1], and with the creation of the dislocation networks at about T = 800˚C [9]. The evolution of the bonding interface thickness was also calculated.…”
Section: Temperature Investigationsupporting
confidence: 90%
“…Previous measurements have been dedicated to thick twistbonded samples 12,13 to study the periodic elastic modulation in two 350 m thick crystals. In this two infinite media geometry, the amplitude of the modulation of atomic position decays exponentially with distance from the interface, and the characteristic thickness has been found to be inversely proportional to the twist angle.…”
Section: Introductionmentioning
confidence: 99%
“…8 X-ray scattering measurements of the strain field in thick bonded wafers with different twist angles twist have been reported previously. 1,9 These measurements were later extended to cover twist from 0.2°to 25°. We found that the thickness of the strained interface is about 0.8 nm for twist Ͼ8°but for smaller angles the thickness is inversely proportional to twist , and for a twist angle of 0.2°, the thickness exceeds 30 nm.…”
mentioning
confidence: 99%
“…The wafer was hydrophobically bonded to a standard Si wafer with a well-defined twist angle twist . 4 After annealing at 1000°C, 9 the SOI bulk crystal and SiO 2 layer were etched away leaving the thin top crystal bonded to the standard wafer.…”
mentioning
confidence: 99%